Q-switched and mode-locked ytterbium-doped fibre lasers with Sb2Te3 topological insulator saturable absorber - Al-Masoodi, Ahmed Hasan Hamood; Ahmad, Fauzan; Ahmed, Mahmoud Hazzaa M.; Al-Masoodi, Abtisam Hasan Hamood; Alani, Ibrahim A.M.; Arof, Hamzah; Harun, Sulaiman Wadi (Institution of Engineering and Technology (IET), 2018)
Q-switched and mode-locked fibre lasers have been successfully demonstrated in ytterbium-doped fibre laser cavity by taking an advantage of the optical absorption of antimony telluride (Sb 2 Te 3 ) material. The Sb 2 Te 3 was embedded into polyvinyl alcohol to function as a saturable absorber (SA). A Q-switching pulses train was obtained by incorporating the SA into the laser ring cavity configured with 3 dB coupler. The Q-switching pulse repetition rate increases from 24.4 to 55 kHz as the pump power is increased from the threshold of 75.4-96.2 mW. The maximum pulse energy of 252.6 nJ is obtained at 82.3 mW pump power. On the other hand, by changing the output coupler to 10 dB coupler, a stable self-started mode-locking operation was then generated at pump power range from 47.8 to 89.4 mW with a fixed repetition rate of 24.2 MHz. At 89.4 mW pump power, the maximum output power and pulse energy are obtained to be around 18.6 mW and 0.8 nJ, respectively. The authors results display that the Sb 2 Te 3 material could also be developed as an effective SA for both Q-switched and mode-locked fibre lasers.